A study of major depressive disorder and quality of life in patients with oral cancer - Kantak, Archana Surajprasad; Vala, Ashokkumar Ukabhai; Panchal, Bharat Navinchandra (International Journal Of Community Medicine And Public Health, 2016)
Background: Head and neck cancer (HNC) is one of the 10 most frequently occurring cancers worldwide, with estimates of over 500,000 new cases annually and one of the 10 leading causes of cancer mortality. Head and neck cancer patients experience among the highest rates of major depressive disorder of all oncology patients. The aim of this study was to find out the frequency of major depressive disorder (MDD) and its association with quality of life in patients with oral cancer. Methods: This is a single-center, cross sectional, observational, questionnaire based study. Seventy consecutive patients, who attended Oncology Outpatient Department of Tertiary care Hospital with diagnosis of Oral cancer were included. Diagnosis of Major Depressive Disorder was done by clinically administered interview as per DSM V. The patients were further assessed for demographic details, HADS-A(Hospital Anxiety and Depression scale for Anxiety),HADS-D (Hospital Anxiety and Depression scale for Depression), FACT H&N QOL (Functional Assessment of Cancer Therapy Head and Neck Quality of Life Scale).Data were analyzed by GraphPad InStat trial version. Proportions were compared by using Chi-square test, HADS-A, HADS-D and FACT H and N QOL scores were compared by Mann-Whitney U test. P value <0.05 was considered to be statistically significant. Results: Frequency of MDD in Oral Cancer patients is 40%.The Patients having Major Depressive Disorder showed higher HADS-A (p<0.0001), HADS-D (p<0.0001)scores and poorer quality of life in all domains of FACT H and N QOL. Conclusions: The Patients with Oral Cancer have higher rates of depression and poor quality of life.